(untitled) (Research, Society and Development, 2021)
In 2020, social isolation resulting from the COVID-19 pandemic posed challenges for the implementation of the teaching-learning process. Faced with this new and unexpected reality, a problem arose: “Can play be a strategy of Social Education in Health with children with cancer in the pandemic?”. Therefore, the objective of this article is to demonstrate how playing can be used as a strategy in the practice of Social Education in Health for children with cancer in Emergency Remote Education (ERT). The methodology of the study was case, with a qualitative approach, through eleven meetings using the Google Meet tool. A literature review was developed on ludic-pedagogical practices in virtual environments and analysis of the activities performed. The theoretical framework was based on Paulo Freire (1967, 1989, 2002), Buber and Schütz (1993), Schütz, Lckmann, and Vygotsky (1988). The results showed that the actions in online environment promoted the construction of knowledge with children and contribute to the initial training of teachers through the extension project. Play ensures access to education during the pandemic period.